Application of 5.8 GHz optical fiber converged communication in transmission line monitoring system - Jie TONG; Yanli LIU; Delong YANG; Hongli LUO; Huan WANG (Dianxin kexue)
When in the depths of the mountains,2G/3G signal is weak or don't exist,or when the high definition video is needed,2G/3G couldn't meet requirements of such high bandwidth,so that communication is intermittent or interrupt,resulting in the condition monitoring data is difficult to transmit reliably to the master station.To solve this problem,2G/3G+5.8 GHz or 5.8 GHz +OPGW converged communication mode was proposed,the signal could be switched automatically to the 5.8 GHz communication mode,and transmits back to the master station after converging the main line and OPGW.Based on the optical fiber converged communication,the transmission line monitoring system and work flow were designed and the application example and the future development prospect were given finally.